Antioxidants: The new frontier for translational research in cerebroprotection - Anurag Tewari; Vidhi Mahendru; Ashish Sinha; Federico Bilotta (Wolters Kluwer Medknow Publications, 2014)
It is important for the anesthesiologist to understand the etiology of free radical damage and how free-radical scavengers attenuate this, so that this knowledge can be applied to diverse neuro-pathological conditions. This review will concentrate on the role of reactive species of oxygen in the pathophysiology of organ dysfunction, specifically sub arachnoid hemorrhage (SAH), traumatic brain injury (TBI) as well as global central nervous system (CNS) hypoxic, ischemic and reperfusion states. We enumerate potential therapeutic modalities that are been currently investigated and of interest for future trials. Antioxidants are perhaps the next frontier of translational research, especially in neuro-anesthesiology.